2022
DOI: 10.1101/2022.01.31.478454
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective inhibition of protein secretion by abrogating receptor-coat interactions during ER export

Abstract: Protein secretion is an essential cellular process that permits cell growth, movement and communication. Traffic of proteins within the eukaryotic secretory pathway is mediated by transport intermediates that bud from one compartment, populated with appropriate cargo proteins, and fuse with a downstream compartment to deliver their contents. Here, we explore the possibility that protein secretion can be selectively inhibited by perturbing protein-protein interactions that drive capture into transport vesicles.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The increased hepatocyte LDLR levels in Surf4 fl/fl Alb-Cre + mice are not accompanied by upregulation of Ldlr mRNA as measured by RNA-seq analysis, consistent with the increase in LDLR abundance being mediated by PCSK9 activity rather than an increase in gene expression. Furthermore, a recent report by Gomez- Navarro et al independently demonstrated that PCSK9 relies on both SEC24A and SURF4 for secretion and that chemical disruption of SEC24A-SURF4 interaction is sufficient to reduce PCSK9 secretion (Gomez-Navarro et al, 2022). Taken together, these data are consistent with the proposed function of SURF4 as a cargo receptor linking PCSK9 in the ER lumen to the SEC24A component of the COPII coat on the cytoplasmic face of the ER (Emmer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The increased hepatocyte LDLR levels in Surf4 fl/fl Alb-Cre + mice are not accompanied by upregulation of Ldlr mRNA as measured by RNA-seq analysis, consistent with the increase in LDLR abundance being mediated by PCSK9 activity rather than an increase in gene expression. Furthermore, a recent report by Gomez- Navarro et al independently demonstrated that PCSK9 relies on both SEC24A and SURF4 for secretion and that chemical disruption of SEC24A-SURF4 interaction is sufficient to reduce PCSK9 secretion (Gomez-Navarro et al, 2022). Taken together, these data are consistent with the proposed function of SURF4 as a cargo receptor linking PCSK9 in the ER lumen to the SEC24A component of the COPII coat on the cytoplasmic face of the ER (Emmer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, it has not been directly observed before in kinetic measurements of ER-to-Golgi transport. A recent study with several cargos demonstrated that 4-PBA selectively inhibited secretion to the medium of client cargos without effects on bulk-flow cargos (39).…”
Section: Alg-2 Activation Increases Copii Sorting Stringency Through ...mentioning
confidence: 99%